Slaughter of small ruminants in developing countries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Manual for slaughtering of small ruminants in developing countries / Clottey, St. John J.A. (1985). Animal Production and Health Paper, No49, FAO, 45 pp.